Improving feeding skills and transition to breastfeeding in early preterm infants: a randomized controlled trial of oromotor intervention - Comuk Balci, Nilay; Takci, Sahin; Seren, H. Canan (Frontiers in Pediatrics, 2023)
Oromotor therapy exercises used for preterm infants in the NICU might promote oral-motor skills and shorten discharge day. This study investigates the impact of an oral-motor therapy program on the successful transition to breastfeeding (BF) and the enhancement of feeding skills in preterm infants below 30 weeks of gestational age who experience feeding intolerance.The intervention group received oral-motor therapy programme for one month, while the control group did not. The feeding skills were evaluated by Early Feeding Skills Assessment Tool (EFS) and Preterm Oral Feeding Readiness Scales (POFRAS). There was a significant difference in EFS and POFRAS scores, transition to bottle feeding at discharge and transition to BF after discharge between babies given oral-motor therapy programme and controls (p<0.05). While the transition time to full enteral feeds did not vary significantly between the groups, noteworthy outcomes were observed in the intervention group, including differences in feeding type at discharge, the nature of feeds at discharge, and the success of transitioning to breastfeeding after discharge. We conclude that the oromotor therapy exercises in NICU improves the quality of sucking, contributes to better oromotor skills and promotes transition to enteral feeding and BF in preterm babies.